The Regression Model Effect of Financial Ratio on Construction and Building Stock Price - Afifuddin, A. (Golden Ratio of Finance Management, 2022)
This study analyzes liquidity, solvency, and profitability of stock prices in construction and building companies listed on the Indonesia Stock Exchange (IDX) for the period 2016-2021. The sample in this study is construction and building companies listed on the Indonesia Stock Exchange (IDX), which is selected based on specific criteria using the Purpose Sampling Method. The analysis used in this study is the Regression Analysis. The results of this study show that liquidity variables have a positive and significant effect on stock prices, and solvency variables have a positive and significant impact on stock prices. In contrast, profitability variables have a positive but insignificant effect on stock prices. The current ratio can be a useful measure of a company’s short-term solvency when it is placed in the context of what has been historically normal for the company and its peer group. It also offers more insight when calculated repeatedly over several periods. What makes the current ratio good or bad often depends on how it is changing. A company that seems to have an acceptable current ratio could be trending toward a situation in which it will struggle to pay its bills. Conversely, a company that may appear to be struggling now could be making good progress toward a healthier current ratio.